Identifying patients at higher risk of pneumonia after lung resection - Liu, Gan-Wei; Sui, Xi-Zhao; Wang, Shao-Dong; Zhao, Hui; Wang, Jun (Journal of Thoracic Disease; Vol 9, No 5 (May 28, 2017): Journal of Thoracic Disease, 2017)
Background: Pneumonia is considered as one of the most common and serious complications after lung resection. The purpose of this study was to identify the risk factors associated with postoperative pneumonia (POP) after lung resection and to develop a scoring system to stratify patients with increased risk of POP. Methods: A retrospective review of a prospective database of patients between September 2014 and June 2016 was carried out. Logistic regression analysis was used to examine the risk factors for POP. Bootstrap resampling analysis was used for internal validation. Regression coefﬁcients were used to develop weighted risk scores for POP. Results: Results revealed that age ≥64 years, smoking (current or previous), high pathological stage, and extent of excision of more than one lobe as risk factors. Logistic regression analysis showed that the predictors of POP were as follows: age ≥64 years, smoking, extent of excision of more than one lobe. A weighted score based on these factors was developed which was follows: smoking (three points), age ≥64 years (four points), and extent of excision of more than one lobe (five points). POP score >5 points offered the best combination of sensitivity (64.7%) and speciﬁcity (83.3%), and an area under receiver operating characteristic (ROC) curve (AUC) of 0.830 [95% confidence interval (CI): 0.746–0.914]. Conclusions: Patients with older age, smoking and extent of excision of more than one lobe have a higher risk for pneumonia after lung cancer surgery. Also, the scoring system helps to guide decision making of POP risk reduction.